A magyarországi járórácspiac környezeti elemzése és szervezeti piaci jellegzetességei - Úr, Norbert; Takácsné György, Katalin; Tamus, Antalné (Acta Carolus Robertus, 2011)
The study examined the relationships between companies in the organizational market, primarily in the steel grating markets and producer companies. We would like to explore a specific product segment analysis of environmental situation. Which competitive advantages prevail in the B2B market. We need to apply the system approach, a long way since the raw material producers to consumers. Analysis of the industrial environment, the strategic planning part. Understanding of the environment, opportunity market development, relationship development, sales development demonstration. Possible methods of research: secondary processing of data, definition of targets, 3-4 group / individual interview preparation. Consumer impressions can get much information in a standardized questionnaire. We would like to ask about 70 to 100 organizational customers. Long-term target: a comparison of the two main strategies grating producer in Hungary.